The effect of suggested jumping training from the International Association of Athletics Federations for Children competitions on raising the level of horizontal jump races among U13 runners - Khalfa , Imededdin (sports creativity, 2025)
Our study aims to identify the effect of the Jumping training from the (IAAF) track and field races for children in raising the level of horizontal jump races among (U13) category runners. Our study community is represented by the clubs of M'sila Association. The study sample included 14 runners from the (JSH) track and field club in a deliberate manner. We relied on the experimental method by designing one group and testing the long and triple jump. We concluded that the proposed training from the track and field races for children had an effect in raising the level of horizontal jump among (U13) category runners. Keywords: IAAF Children's Athletics Competitions , Jumping, long jump, triple jump